Location of high-rise buidings in Wrocław - Zakrzewska-Półtorak, Alicja (Lokalizacja budynków wysokościowych we Wrocławiu, 2017)
The aim of the paper is to discuss the arrangement of the existing and new high-rise buildings in Wrocław, as well as to determine the impact of their location on spatial order. The author uses a descriptive method, simple statistical methods, a deductive method and empirical inference. The subject of the research is Wrocław, with special attention to high-rise objects location. The basic research covers the period of 2010-2017. The question of planning and building high-rise objects was discussed in Wrocław studies of conditions and directions of spatial development (2010 and 2017). As the recent years reveal, the number of very high buildings in Wrocław is not on the rise. However, Wrocław is prepared for their arrival.
Biblioteka Regionalisty, 2017, Nr 17, s. 119-126
Keywords: Wrocław; high-rise building; spatial order; urban spatial structure; study of conditions anddirections of spatial development of the commune; budynek wysokościowy; ład przestrzenny; struktura przestrzenna miasta; studium uwarunkowań i kierunków zagospodarowania przestrzennego gminy